Elicitation of galanthamine production by leucojum aestivum shoots grown in temporary immersion system. (17th January 2013) - Schumann, Anika; Torras‐Claveria, Laura; Berkov, Strahil; Claus, Diana; Gerth, André; Bastida, Jaume; Codina, Carles
<x xml:space="preserve">Abstract</x> The influence of different elicitors (copper sulfate, silver nitrate, salicylic acid and methyl jasmonate), on both the growth and alkaloid production of Leucojum aestivum shoots grown in a temporary immersion system was studied. Seven Amaryllidaceae alkaloids and three protoalkaloids were quantitatively determined by GC‐MS analysis in leaves and bulblets, separately. Methyl jasmonate was found to significantly improve the production of galanthamine (GAL) in both leaves and bulblets. The content of GAL released to the liquid nutrient medium was also measured. The release of GAL into the liquid medium took place mainly in the first 2 weeks determined by harvesting the liquid nutrient medium after 2 weeks and measuring the GAL content (1st subculturing step). © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29: 311–318, 2013